A study of the association of Fermi sources with massive young galactic objects - Munar Adrover, P. (2011)
Massive protostars have associated bipolar outflows that can produce strong shocks when they interact with the surrounding medium. At these shocks, particles can be accelerated up to relativistic energies. Relativistic electrons and protons can then produce gamma-ray emission, as some theoretical models predict. To identify young galactic objects that may emit gamma rays, we crossed the Fermi First Year Catalog with some catalogs of known massive young stellar objects (MYSOs), early type stars, and OB associations, and we implemented Monte Carlo simulations to find the probability of chance coincidences. We obtained a list of massive MYSOs that are spatially coincident with Fermi sources. Our results indicate that ~70% of these candidates should be gamma-ray sources with a confidence of ~5σ. We studied the coincidences one by one to check the viability of these young sources as potential counterparts to Fermi sources and made a short list of best targets for new detailed multifrequency observations. The results for other type of young galactic objects are not conclusive.